The Effect Of Stress and Optimism on Resilience for Parents with Children Leukemia at Ulin Hospital Banjarmasin: Pengaruh Stres dan Optimisme Terhadap Resilience pada Pada Orang Tua dengan Anak Penyandang Leukemia Di RSUD Ulin Banjarmasin - Sari, Rani Normaya; Fetriyah, Umi Hanik; Muhammad Riduansyah (LPPM STIKES Guna Bangsa, 2024)
Childhood Cancer is a life-threatening disease and the leading cause of child death in low- and middle-income countries. Families having children with cancer can have a negative impact on the well-being of parents. Long leukemia treatment has an impact on parents, therefore resilience is needed. Several factors affect resilience, namely stress and optimism. Knowing the relationship between stress and optimism on the resilience of mothers who have children with leukemia at Ulin Hospital, Banjarmasin. Analytical survey design and Cross-Sectional design. The sample is a mother who has 30 children with leukemia using a purposive sampling technique. The instrument uses a Stress Scale (PSS) questionnaire. Optimism uses the Life Orientation Test – Revised (LOT-R) questionnaire, resilience uses The Corner Davidson Resilience Questionnaire (CD-RISC) which has been tested for validity and reliability. Univariate data analysis was performed to determine the frequency and percentage, and bivariate was performed using Kalmogorov-Smirnov to determine the relationship between variables.